Introducing just sustainabilities policy, planning, and practice - Agyeman, Julian (London Zed Books, 2013)
This unique and insightful text offers an exploration of the origins and subsequent development of the concept of just sustainability. It discusses key topics, such as food justice, the democratization of our streets, social inclusion, and alternative economic models, with a specific focus on solutions-oriented policy and planning initiatives that specifically address issues of equity and justice within the context of developing sustainable communities.
Includes index
Keywords: Sustainable development--Social aspects